Development and validation of a simple, cost-effective competitive allele-specific PCR assay for largescale screening and detection of FecB mutation in sheep - Kathiravan Periasamy; Rudolf Pichler; Saravanan Ramasamy; Rajesh Kumar Somasundaram; Muladno Basar; Atanaska Teneva; Amadou Traore; Arnaud S. R. Tapsoba; Mohammed O. Faruque; Seyed Abbas Rafat; Tanveer Hussain (PLoS ONE, 2025)
The Booroola fecundity (Fec B ) gene, a mutation in the bone morphogenetic protein receptor-1B (BMPR1B), is known to increase ovulation rate and litter size in sheep. Efficient and accurate, large-scale detection of this single nucleotide polymorphism (SNP) is critical for marker assisted introgression/selection programs for genetic improvement of prolificacy. This study aimed to develop and validate a robust, cost-effective, and high-throughput genotyping assay for detecting the FecB mutation across diverse sheep populations globally. A competitive allele-specific PCR (KASP) assay targeting the A746G nucleotide substitution in BMPR1B gene was designed and tested on a diverse panel of 224 individuals across 22 sheep breeds and validated against direct sequencing. The KASP genotyping results showed 100% concordance with sequence data, with clear fluorescence-based discrimination of homozygous wild-type Fec ++ (AA), heterozygous Fec B+ (AG), and homozygous mutant Fec BB (GG) genotypes. The assay was compatible across three real-time PCR platforms, BioRad CFX96, Roche LightCycler 480 II, and ABI QuantStudio 6 demonstrating reproducible genotyping and cross-platform interoperability. Subsequently, the KASP assay was applied to a global screening of 1471 sheep from 47 breeds in 14 countries for further validation of the assay. The mutation was not observed in the sheep samples investigated from Africa, Europe, Latin America, and West Asia, whereas it was polymorphic or fixed in certain populations from South (India and Bangladesh) and Southeast Asia (Indonesia). Notably, native Bangladeshi sheep exhibited high frequencies of the Fec B allele, with some populations (e.g., Bangladesh Central) nearing fixation, reflecting possible selection for high prolificacy. In conclusion, the validated KASP assay offers a powerful, scalable tool for the rapid genotyping of the Fec B mutation, enabling efficient screening and incorporation of prolificacy traits in sheep breeding programs worldwide.